Una propuesta metodológica para el estudio del paisaje integrado - Ibarra Benlloc, Paloma (Geographicalia, 2017)
A methodology to the study of the integrated landscape is shown, based on a geographical and systematic conception of the landscape. The study is thought at half scale (1/25.000 - 1/50.000) and is composed of four big stages: lª) The landscape elements analysis; 2ª) Delimitation and characterisation of the landscape units; 3ª) Explanatory landscape factors; 4ª) Diagnosis about the landscape dynamic.